High HIV Positivity Rates Following Large-Scale HIV Self-Testing Implementation in Zimbabwe, 2018–2020 - Muchedzi, Auxilia; Mpofu, Mulamuli; Mudzengerere, Fungai H.; Bateganya, Moses; Mavimba, Tarirai; Satti, Hind; Dhliwayo, Rumbidzai; Zulu, Tinashe; Tapera, Talent; Samushonga, Tendai; Nyagura, Tendai; Ncube, Getrude; et al. (Frontiers in Public Health, 2021)
Introduction: HIV self-testing (HIV-ST) is an innovative strategy to increase HIV case identification. This analysis shares the outcomes of HIV-ST implementation within the Zimbabwe HIV Care and Treatment (ZHCT) project for the period October 2018–March, 2020. Materials and Methods: We extracted HIV-ST data for the period October 2018 to March 2020 from the project database and assessed (1) the proportion of reactive HIV-ST results; (2) the concordance between reactive HIV-ST results against rapid confirmatory HIV tests using Determine™ and Chembio™ in parallel; and (3) the monthly contribution of HIV-ST to total HIV positive individuals identified within project. The Chi-square test was used to assess for statistical differences in HIV positivity between age groups, by sex and district; as well as the difference in HIV positivity between the HIV-ST and index and mobile testing strategies. Findings: Between October 2018 and March 2020, the ZHCT project distributed 11,983 HIV-ST kits; 11,924 (99.8%) were used and 2,616 (21.9%) were reactive. Of the reactive tests, 2,610 (99.8%) were confirmed HIV positive giving a final positivity rate of 21.9%, and a concordance rate of 99.8% between the HIV-ST results and the confirmatory tests. Proportion of reactive results differed by age-groups (p < 0.001); with the 35–49 years having the highest positivity rate of 25.5%. The contribution of HIV-ST to total new positives increased from 10% in October 2018 to 80% at the end of March 2020 (p < 0.001). Positivity rates from HIV-ST were significantly different by age-groups, sex and district (p = 0.04). Additionally, index and mobile testing had a higher positivity rate compared to HIV-ST (p < 0.001). Conclusion: The ZHCT project has successfully scaled up HIV self-testing which contributed significantly to HIV case finding. Countries should consider using the lessons to scale-up the intervention which will contribute in reaching under-served and undiagnosed populations.